Responder
4. В треугольнике \( ABC \), угол \( C = 85^\circ \) и соотношение углов \( A : B = 2 : 3 \). Разность \( \angle C - \angle A = 47^\circ \).
5. В треугольнике \( ABC \), соотношение углов \( A : B : C = 3 : 4 : 5 \). Разность \( \angle C - \angle B = 15^\circ \).
6. В треугольнике \( ABC \), \( \angle A = \angle B - 21^\circ \) и \( \angle B = \angle C - 18^\circ \). Градусная мера угла \( C = 79^\circ \).
7. В треугольнике \( ABC \), \( \angle B = \angle A + 29^\circ \) и \( \angle C = \frac{3}{4} \angle B \). Градусная мера угла \( C = 57^\circ \).
Solución
Alright, I need to solve these geometry problems involving triangles and angle measures. Let's tackle them one by one.
**Problem 4:**
In triangle \( ABC \), angle \( C = 85^\circ \) and the ratio of angles \( A : B = 2 : 3 \). Find the difference \( \angle C - \angle A \).
First, I recall that the sum of angles in a triangle is \( 180^\circ \). So, \( \angle A + \angle B + \angle C = 180^\circ \).
Given:
- \( \angle C = 85^\circ \)
- \( \angle A : \angle B = 2 : 3 \)
Let's denote \( \angle A = 2x \) and \( \angle B = 3x \).
So, \( 2x + 3x + 85^\circ = 180^\circ \)
\( 5x + 85^\circ = 180^\circ \)
\( 5x = 180^\circ - 85^\circ \)
\( 5x = 95^\circ \)
\( x = 19^\circ \)
Therefore:
- \( \angle A = 2x = 38^\circ \)
- \( \angle B = 3x = 57^\circ \)
Now, the difference \( \angle C - \angle A = 85^\circ - 38^\circ = 47^\circ \).
**Problem 5:**
In triangle \( ABC \), the ratio of angles \( A : B : C = 3 : 4 : 5 \). Find the difference \( \angle C - \angle B \).
Again, the sum of angles in a triangle is \( 180^\circ \).
Given:
- \( \angle A : \angle B : \angle C = 3 : 4 : 5 \)
Let's denote:
- \( \angle A = 3x \)
- \( \angle B = 4x \)
- \( \angle C = 5x \)
So, \( 3x + 4x + 5x = 180^\circ \)
\( 12x = 180^\circ \)
\( x = 15^\circ \)
Therefore:
- \( \angle A = 45^\circ \)
- \( \angle B = 60^\circ \)
- \( \angle C = 75^\circ \)
The difference \( \angle C - \angle B = 75^\circ - 60^\circ = 15^\circ \).
**Problem 6:**
In triangle \( ABC \), \( \angle A = \angle B - 21^\circ \) and \( \angle B = \angle C - 18^\circ \). Find the measure of angle \( C \).
Let's denote:
- \( \angle A = \angle B - 21^\circ \)
- \( \angle B = \angle C - 18^\circ \)
From the second equation, \( \angle C = \angle B + 18^\circ \)
Substitute \( \angle B \) from the second equation into the first:
\( \angle A = (\angle C - 18^\circ) - 21^\circ = \angle C - 39^\circ \)
Now, sum of angles:
\( \angle A + \angle B + \angle C = 180^\circ \)
\( (\angle C - 39^\circ) + (\angle C - 18^\circ) + \angle C = 180^\circ \)
\( 3\angle C - 57^\circ = 180^\circ \)
\( 3\angle C = 237^\circ \)
\( \angle C = 79^\circ \)
**Problem 7:**
In triangle \( ABC \), \( \angle B = \angle A + 29^\circ \) and \( \angle C = \frac{3}{4} \angle B \). Find the measure of angle \( C \).
Given:
- \( \angle B = \angle A + 29^\circ \)
- \( \angle C = \frac{3}{4} \angle B \)
Sum of angles:
\( \angle A + \angle B + \angle C = 180^\circ \)
Substitute \( \angle B \) and \( \angle C \):
\( \angle A + (\angle A + 29^\circ) + \frac{3}{4}(\angle A + 29^\circ) = 180^\circ \)
Let's denote \( \angle A = x \):
\( x + (x + 29^\circ) + \frac{3}{4}(x + 29^\circ) = 180^\circ \)
\( x + x + 29^\circ + \frac{3}{4}x + \frac{87^\circ}{4} = 180^\circ \)
Combine like terms:
\( 2x + \frac{3}{4}x + 29^\circ + 21.75^\circ = 180^\circ \)
\( \frac{11}{4}x + 50.75^\circ = 180^\circ \)
\( \frac{11}{4}x = 129.25^\circ \)
\( x = \frac{129.25^\circ \times 4}{11} \)
\( x = \frac{517^\circ}{11} \)
\( x \approx 47.0^\circ \)
Now, \( \angle B = x + 29^\circ = 47^\circ + 29^\circ = 76^\circ \)
\( \angle C = \frac{3}{4} \times 76^\circ = 57^\circ \)
So, \( \angle C = 57^\circ \).
Revisado y aprobado por el equipo de tutoría de UpStudy
Explicar
Simplifique esta solución